2007
DOI: 10.1245/s10434-007-9435-3
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoxic Environment in Tumor-Stromal Cells Accelerates Pancreatic Cancer Progression via the Activation of Paracrine Hepatocyte Growth Factor/c-Met Signaling

Abstract: These data suggest that the HGF/c-Met signaling via HIF-1alpha ?may therefore negatively affect the prognosis in patients with pancreatic cancer, and targeting tumor stroma under hypoxia might thus be potentially useful as a novel therapy for this cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 28 publications
7
76
0
Order By: Relevance
“…[3][4][5][6][7][8] This association has also been shown for PDAC, where a more hypoxic phenotype is associated with a worse prognosis. 38,39 We hypothesize that the clinical outcome for patients treated with the triplet treatment may be more favorable than doublet nab-paclitaxel and gemcitabine, given the multiple therapeutic modalities employed including hypoxia-selective targeting.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8] This association has also been shown for PDAC, where a more hypoxic phenotype is associated with a worse prognosis. 38,39 We hypothesize that the clinical outcome for patients treated with the triplet treatment may be more favorable than doublet nab-paclitaxel and gemcitabine, given the multiple therapeutic modalities employed including hypoxia-selective targeting.…”
Section: Discussionmentioning
confidence: 99%
“…Low microvascular density (MVD) and reduced blood flow have been shown to be signs of tumor aggressiveness [10][11][12], and high MVD in peripheral hot spots has been found to correlate with poor prognosis, suggesting that highly heterogeneous microcirculation aggravates the outcome [6,13]. It has also been revealed that poor prognosis is associated with severe hypoxia in the primary tumor [14][15][16]. Moreover, the interstitial fluid pressure (IFP) has been reported to be elevated [17][18][19], and it has been suggested that highly elevated IFP together with a dense and extensive stroma may cause resistance to treatment by inhibiting the distribution of chemotherapeutic agents [19].…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that tumor-stromal cell interactions under hypoxia increase the invasiveness of pancreatic cancer cells through up-regulated HGF/c-Met signaling via HIF-1· (31). We further reported a significant correlation between the HIF-1· expression and poor prognosis in patients with pancreatic cancer (32). Other studies have also reported a significant association between HIF-1· expression and prognosis in a variety of human cancers including stomach (17), esophagus (18), pancreas (19), lung (20), breast (21), upper urinary tract (22), uterine cervix (23) and ovarian cancer (24).…”
Section: Discussionmentioning
confidence: 81%
“…Immunohistochemical staining was performed according to the procedures described in a previous study with slight modifications (31,32). Briefly, the paraffinembedded samples were cut into 4-μm thick sections and then were deparaffinized in xylene and rehydrated in a graded series of ethanol.…”
Section: Patientsmentioning
confidence: 99%